Alfonso Maria de Liguori, Carteggio. 1 :1724-1743, oprac. G. Orlandi, Edizioni di Storia e Letteratura, Roma 2004, ss. 840. - Maciej Sadowski (Folia Historica Cracoviensia, 2006)
Recenzja:  Alfonso Maria de Liguori, Carteggio. 1 :1724-1743, oprac. G. Orlandi, Edizioni di Storia e Letteratura, Roma 2004, ss. 840.